1998
DOI: 10.11606/issn.2594-5904.rpef.1998.139526
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics in laboratorial tests and blood lactate response in three fights in juvenile, junior and senior judo players

Abstract: RESUMOO objetivo deste estudo foi verificar, em judocas masculinos das classes Juvenil-A (15 a 17 anos de idade; n = 6), Júnior (18 a 20 anos de idade; n = 5) e Sênior (acima de 21 anos de idade; n = 4), a relação entre variáveis fisiológicas e metabólicas em testes laboratoriais e em situação de luta e compará-las. Para isso foram realizados testes em três situações distintas: teste em esteira rolante (TE); teste em cicloergômetro para membros superiores (TCMS); situação de luta (SL). A partir destes testes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Therefore, athletes of grappling and percussion fights need to have an efficient glycolytic metabolism for energy transfer. This because many times these fights calls for movements of high power to perform muscular actions 9 , and they also need an aerobic capacity adequate to sustain the performance during the fighting 10 . Thus, it is suggested that the ability of some wrestlers to protrude in their specific sports of combat can be directly related to genetic predisposition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, athletes of grappling and percussion fights need to have an efficient glycolytic metabolism for energy transfer. This because many times these fights calls for movements of high power to perform muscular actions 9 , and they also need an aerobic capacity adequate to sustain the performance during the fighting 10 . Thus, it is suggested that the ability of some wrestlers to protrude in their specific sports of combat can be directly related to genetic predisposition 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Research comparing the UbWt performance between juvenile, junior and senior judoists has shown that there were significant differences (p < 0.05) in mean absolute power and peak absolute power between juvenile and senior groups [74]; however, no differences were noted when the results were relativised to body mass. The main study outcome reported that athletes above seventeen display anaerobic power similar to junior and senior athletes with regard to body mass [74]. Therefore, we must be careful which results (absolute or relative) we compare to the established normative values.…”
Section: Discussionmentioning
confidence: 92%
“…Drigo et al (1996) verificaram respostas semelhantes de lactato em lutas (três lutas de dois minutos e 90 segundos de intervalo) simuladas de solo (6.7 ± 2.8mmol/l) e lutas de projeção (6.5 ± 2.8mmol/l). Entretanto, Franchini et al (1998Franchini et al ( , 20012009) (Franchini et al, 2001). Mesmo assim, conforme o estudo de validação do SJFT (Sterkowicz et al, 1999), o índice do teste obteve boa correlação com índices de aptidão aeróbia e anaeróbia.…”
Section: Introductionunclassified